Actantial roles of workers in leftist news discourse - Blanco, Desiderio (1986)
The spontaneous reading of the journalistic discourse of the Peruvian left (Marka's diary) suggests that there must be a correlation between the theoretical discourse of Marxism and the daily discursive practice. In the search for this correlation I have begun to investigate the role that journalistic discourse assigns to workers in the text of social life. The hypothesis of this work assumes that the coincidences will occur in the plane of the statement, while the discrepancies will appear at the level of enunciation. Throughout the analysis I will point out the ones and the others, comparing them with the classic texts of Marxism.